Metastatic Giant Cell Tumor Causing Small Bowel Intussusception on 18F-FDG PET/CT. (6th November 2022) - Walcutt, Julie E.; Johnson, Craig M.; Ly, Quan P.; Downey, Ryan T.
Abstract: An 89-year-old man with a history of a malignant giant cell tumor of soft parts in the right thigh with recurrent/metastatic tumor in the right pelvis was found to have pulmonary nodules concerning for metastatic disease. Subsequent PET/CT unexpectedly demonstrated a right lower quadrant intussusception with a hypermetabolic mass serving as a lead point. Pathology of the resected mass causing the intussusception was compatible with a metastasis from the patient's malignant giant cell tumor of soft parts.